2017
DOI: 10.1021/jacs.7b05193
|View full text |Cite
|
Sign up to set email alerts
|

Raman Optical Activity Reveals Carotenoid Photoactivation Events in the Orange Carotenoid Protein in Solution

Abstract: The orange carotenoid protein (OCP) plays an important role in photoprotection in cyanobacteria, which is achieved by the photoconversion from the orange dark state (OCP) to the red active state (OCP). Using Raman optical activity (ROA), we studied the conformations of the carotenoid chromophore in the active sites of OCP and OCP. This ROA measurement directly observed the chromophore conformation of native OCP in solution, and the measurement of OCP first demonstrated the ROA spectroscopy for the transient sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
2
43
0
2
Order By: Relevance
“…No secondary structure fingerprint could be identified in the 532‐nm excited rROA spectra of met‐Mb nor imidazolylmet‐Mb, because the resonance with the Q absorption bands of the haem chromophore (see Figure ) led to the selective enhancement of the porphyrin vibrations . On top of that, the concentration of 0.284‐mM Mb (5 mg ml −1 ) used for the measurements was too low to actually detect signals from the globin backbone, further confirming the nature of the rROA signals . The main challenge to understanding the spectral trends currently is to link the conformational modification occurring at the chromophore during ligand binding with the rROA spectral changes.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…No secondary structure fingerprint could be identified in the 532‐nm excited rROA spectra of met‐Mb nor imidazolylmet‐Mb, because the resonance with the Q absorption bands of the haem chromophore (see Figure ) led to the selective enhancement of the porphyrin vibrations . On top of that, the concentration of 0.284‐mM Mb (5 mg ml −1 ) used for the measurements was too low to actually detect signals from the globin backbone, further confirming the nature of the rROA signals . The main challenge to understanding the spectral trends currently is to link the conformational modification occurring at the chromophore during ligand binding with the rROA spectral changes.…”
Section: Resultsmentioning
confidence: 95%
“…In the rRaman spectral region, around 1,000 cm −1 hydrogen‐out‐of‐plane modes can be observed. Fujisawa et al reported in their study on the orange carotenoid protein that the intensity of the rROA band at 980 cm −1 represents a good estimation of the distortion of the chromophore . Despite the structure of the porphyrin differs substantially from that one of the orange carotenoid protein and a direct comparison between the two molecules cannot be done, the lack of good S/N details in the ROA spectrum of imidazolyl‐metMb in correspondence of the Raman bands at 1,002 and 976 cm −1 where the hydrogen‐out‐of‐plane modes can be detected may indicate that the binding of imidazole does not increase the level of distortion of the haem plan with respect to the unbound protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being structurally sensitive,t he HOOP band [37,38] can be considered as evidence for the presence of deuterated (more bent) bCm olecules in the supramolecular mixed arrangement, which gives achiral response.Moreover,anincrease in the intensity of the HOOP band can also be seen in the Raman spectra of the bCmonomer and its aggregate before, as well as after deuteration ( Figure S5). However,b ased on the vibrational analysis of 11,12-dideuterioretinal, [40] it can be seen that the HOOP band is enhanced for deuterated derivatives,w hich confirms as ubstantial deuterium-induced change in the molecular structure of bC-d compared with bC.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[9] In contrast to bC, amodel system built from the combination of achiral bC(80 %) and chiral aC(20 %) shows ac hiral signal in the ECD and RROA spectra (Figure 2, right). [37,38] Therefore,i ts occurrence is most likely related to the bending of the carotenoid chain in the bC/ aCmodel, which probably comes from aC, whose structure is more bent ( Figure S2). [37,38] Therefore,i ts occurrence is most likely related to the bending of the carotenoid chain in the bC/ aCmodel, which probably comes from aC, whose structure is more bent ( Figure S2).…”
mentioning
confidence: 99%